Fencing in the practice of revenue management - Zhang, Michael (Henry Stewart Talks, 2009)
Business issues surrounding fences, Issues related to the segmentation process, segmentation enforcement and the implementation of fencing in revenue management, Presentation of taxonomy of fences, Specific discussion of the impact of imperfect fences